International Pediatric Otolaryngology Group (IPOG) consensus recommendations: Evaluation and management of congenital tracheal stenosis. (October 2022) - Sidell, Douglas R.; Meister, Kara D.; de Alarcon, Alessandro; Boudewyns, An; Brigger, Matthew; Chun, Robert; Fayoux, Pierre; Goudy, Steven; Hart, Catherine K.; Hewitt, Richard; Hsu, Wei-Chung; Javia, Luv R.; et al.
Abstract: Objectives: To outline an expert-based consensus of recommendations for the diagnosis and management of pediatric patients with congenital tracheal stenosis. Methods: Expert opinions were sought from members of the International Pediatric Otolaryngology Group (IPOG) via completion of an 18-item survey utilizing an iterative Delphi method and review of the literature. Results: Forty-three members completed the survey providing recommendations regarding the initial history, clinical evaluation, diagnostic evaluation, temporizing measures, definitive repair, and post-repair care of children with congenital tracheal stenosis. Conclusion: These recommendations are intended to be used to support clinical decision-making regarding the evaluation and management of children with congenital tracheal stenosis. Responses highlight the diverse management strategies and the importance of a multidisciplinary approach to care of these patients.